Effects of an eight-week progressive distance running program on isolated electrocardiographic and vectorcardiographic parameters in untrained college males - Leroy La Forge, Ralph Jr. (My University, 1975)
This study was designed to determine specific electrocardiographic and vectorcardiographic effects of an eight-week progressive distance running program in untrained college males. Specific objectives were to measure changes in (1) resting heart rate, (2) Q-T interval, QRS duration, and QRS and T wave height in lead II and V4 of the electrocardiogram, (3) maximum QRS and T vector axis in three planes of the vectorcardiogram, (4) QRS-T angle and maximum QRS and T vector magnitude in the frontal plane of the vectorcardiogram, and (5) Balke treadmill test exercise tolerance.
Keywords: Running; Heart beat; Exercise - Physiological aspects